Mechanism of triptolide regulating proliferation and apoptosis of hepatoma cells by inhibiting JAK/STAT pathway - Wang Guanglian; Zhu Zhenxin; Sun Zhengang; Yang Zhiqi (Open Life Sciences)
This study was to analyze the effect of triptolide (TPL) on proliferation, apoptosis, and the relationship between TPL and the Janus kinase/signal transducer and activator of transcription signaling pathway in hepatoma cells. HepG2 cell line was selected as the experimental object and divided into control, low-dose TPL, medium-dose TPL, and high-dose TPL group. The control group did not receive any drug treatment, while the low, medium, and high-dose groups were treated with TPL at concentrations of 0.02, 0.05, and 0.10 μM, respectively. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide, flow cytometry, and western blot were used to detach the TPL effect and mechanism. The cell proliferation inhibition rate in each dose group of TPL was lower than that in the control group, and the inhibition rate of cell proliferation increased with the increase of TPL dose (P < 0.05). The apoptosis rate of TPL in each dose group was higher than that in the control group, and the apoptosis rate increased with the increase of TPL dose (P < 0.05). The expression of phosphorylated Janus kinase 1 (p-JAK1) and phosphorylated signal transducer and activator of transcription 3 (p-STAT3) protein in cells of each dose group of TPL was lower than that in the control group, and the expression of p-JAK1 and p-STAT3 protein decreased with the increase of TPL dose (P < 0.05). The apoptosis rate of 10 ng/mL transforming growth factor-beta + high-dose group was reduced than that in the high-dose group, and the expression of p-JAK1 and p-STAT3 protein was higher than that in the high-dose group (P < 0.05). The activity of B-cell lymphoma/leukemia-2-associated X protein (Bax) protein and cysteine aspartic acid protease (Caspase)-3/9 in TPL cells at each dose was raised than that in the control group, and the expression of B-cell lymphoma/leukemia-2 (Bcl-2) protein was decreased than that in the control group. With the increase of TPL dose, the activity of Bax protein and Caspase-3/9 increased, and the Bcl-2 protein decreased (P < 0.05). As an anti-liver cancer agent, TPL inhibits the proliferation of hepatocellular carcinoma cells and promotes apoptosis. The mechanism may involve inhibiting Janus kinase 1/signal transducer and activator of transcription 3 pathway and activation of apoptosis-related pathways.